Clinical Tolerability and Safety of Tramadol in Hospitalized Patients. (28th September 2020) - Mohan, Nikhil; Edmonds, Kyle P.; Ajayi, Toluwalase A.; Atayee, Rabia S.
Abstract: Tramadol is a schedule IV, monoaminergic and μ-opioid-receptor analgesic with unique pharmacology properties. Though it is well established and widely utilized, there is little guidance on tramadol's place in therapy, including tolerability, safety and monitoring guidelines. Retrospective chart review of 250 patients who received oral tramadol during their hospitalization from January 1, 2018 to December 31, 2018. Of the 250 patients, 10.8% had cancer as their primary diagnosis while 8.8% were admitted for hematologic reasons. 79.1% of patients had acute pain. Palliative care consult or ICU admission resulted in significant discontinuation of tramadol (p < 0.05 odds ratio 6.88, 2.39). There was no significant relationship of hypoglycemia when evaluating days on tramadol, total number of doses on tramadol, and MEDD start and end (p = 0.36, 0.88, 0.15, 0.23 consecutively). The longer that patients were on tramadol and the more doses they received during their inpatient stay, the greater risk of a severe drug-drug interaction (p < 0.05; R 0.29). In hospitalized patients, the risk of major and severe drug-drug interactions with tramadol increased with dose and duration. Hospital medicine, bone marrow transplant, and emergency medicine teams predominantly used tramadol.